TianGong database—an open-source, ILCD entry-level life cycle unit process database of china - Ming Xu; Weiqiang Chen; Yutao Wang; Lei Shi; Zhi Cao; Huimin Chang; Chang Chen; Xiangbin Ding; Jianwei Du; Huabo Duan; Kai Fang; Cuiyang Feng; et al. (Journal of Industrial Ecology, 2026)

Acute Stress Facilitates Cognitive Control in Healthy Men: an fNIRS Study - Xiaoman Wang; Heming Gao; Mingming Qi (Brain Topography, 2026)

The effectiveness of Go/Nogo dual-task is modulated by SOA and Go/Nogo ratio - Xiaoman Wang; Guiqin Ren; Heming Gao; Mingming Qi (Behavioural Processes, 2025)

The 3PM transformation potential of minimal residual disease in solid tumor management: a bibliometric analysis and review - Yining Chen; Xin Li; Suya Zhao; Yuchong Zhang; Haixu Wang; Fangjian Na; Qi Guan; Zhi Li; Heming Li; Mingfang Zhao (EPMA Journal, 2025)

Highly efficient catalytic hydrogenation of nitrobenzene on cobalt- immobilized nitrogen-doped carbon: A dual-sites synergistic effect between cobalt single atoms and cobalt nanoparticles - Heming Qi; Xingling Wang; Ming Lei; Wenyu Fan; Shuangshuang Huang; Lihua Zhu; Heqing Tang (Chemical Engineering Journal, 2024)

Dietary sinensetin and polymethoxyflavonoids: Bioavailability and potential metabolic syndrome-related bioactivity - Mutang Zhang; Hao Jiang; Shaobi Ou; Min Qian; Heming Qi; Junping Chen; Xiaofang Zeng; Weidong Bai; Gengsheng Xiao (Critical Reviews in Food Science and Nutrition, 2024)

Regional water-energy-carbon footprint in the context of sustainable development based on EE-MRIO: cases of Jiangsu, Zhejiang and Shanghai - Huanyu Wang; Qiang Yue; Rui Liu; Yujie Zhang; Heming Wang; Qi Wang (Environment, Development and Sustainability, 2024)

Analysis of iron and steel production paths on the energy demand and carbon emission in China’s iron and steel industry - Qiang Yue; Xicui Chai; Yujie Zhang; Qi Wang; Heming Wang; Feng Zhao; Wei Ji; Yuqi Lu (Environment, Development and Sustainability, 2023)

Co‐benefits analysis of industrial symbiosis in China's key industries: Case of steel, cement, and power industries - Qi Zhang; Ting Xiang; Wei Zhang; Heming Wang; Jing An; Xiuping Li; Bing Xue (Journal of Industrial Ecology, 2022)
Accelerating the construction of ecological civilization in the industrial field and guiding the transformation of industry toward a green direction have become a national development strategy. Promoting the coordinated development of energy‐intensive industries such as steel, cement, and power is a key breakthrough in achieving the green transformation of various industries. This study has designed a steel–cement–power polygeneration system with the collaborative utilization of solid waste resources as the ecological link point. Four scenarios, including business‐as‐usual, optimization of product structure, low‐carbon technology application, and policy advancement (PAD), were established to assess the overall energy‐saving and emissions reduction potential of the steel–cement–power polygeneration system from 2015 to 2050. The results show that product structure adjustment and industrial symbiosis have a significant impact on energy saving and emission reduction of key industries. In 2050, the total energy consumption and carbon emissions of the polygeneration system could reach 38,697.64 PJ and 3766.73 Mt CO 2 . Based on the scenario analysis, the production and use of solid waste in the polygeneration system and the economic benefits are also discussed. Under the PAD scenario, by 2050, the proportion of fly ash as cement raw material will increase to 41%, while the supply of blast furnace slag may be insufficient, and the comprehensive utilization of solid waste can bring economic benefits of 238.32 billion Yuan to the system.

Revealing the Precise Role of Calretinin Neurons in Epilepsy: We Are on the Way - Yingbei Qi; Heming Cheng; Yi Wang; Zhong Chen (Neuroscience Bulletin, 2022)

Response inhibition and memory updating in the count/nocount task: an ERP study - Zhuyun Zhang; Jingyan Jing; Mingming Qi; Heming Gao (Experimental Brain Research, 2021)

The effect of mild acute psychological stress on attention processing: an ERP study - Mingming Qi; Heming Gao; Guangyuan Liu (Experimental Brain Research, 2018)